Komunikasi Pemerintahan : Mengirim dan Menerima Informasi Tugas dan Informasi Publik - Ulber Silalahi (Centre for Public Policy and Management Studies, 2004)
Government communication is one of the important element in public organization, which is become a part of organizational communication. In the context of organizational communication, government communication can be separated by internal communication and external communication. Internal communication have a lot of purposes like sending and receiving task information between administrator and staff External communication intend to sending public information from administrator and staff to public and privat sector, instrument of administrative accountability to the public and also accomodating public opinion. In the Orde Baru era, there were dominated kind of the way which is communication exist, that are downward and upward communication. Government communication in good governance dominating by responsiveness, transparency, participation, and accountability. Blockages in communication could be eliminated by using the ‘right’ language, eliminating barriers and having knowledge about the audience, the message and the medium.Kata kunci : government communication, internal, external communication